Interpersonal Communication Patterns in Creating Interreligious Tolerance in Parapat Village, Simalungun District - Syarifah, Syarifah; Kholil, Syukur; Sumanti, Solihah Titin (International Journal of Cultural and Social Science, 2023)
Interpersonal communication will never be separated from humans with cultural or religious backgrounds, if communication cannot work effectively then conflicts can arise between community groups. So that this does not happen, it is necessary to instill mutual tolerance. The focus of the problem in this research is how the patterns of interpersonal communication in creating tolerance between religious communities in Parapat Sub-District, Simalungun Regency and whether there are obstacles to patterns of interpersonal communication in creating inter-religious tolerance in Parapat Sub-District, Simalungun Regency. This research uses a qualitative type of descriptive approach. The subjects in this study are people who live in Parapat Village, Simalungun Regency, in this case I took 6 residents using a purposive technique, namely with predetermined criteria. The theory used in this study is social penetration and self-disclosure. Which this theory explains how the process of relating to other people and self-disclosure in order to establish good interactions and avoid misunderstandings. The results of this study indicate that the communication pattern used in Parapat Village is an interactional communication pattern or a reciprocal relationship in communication. Obstacles Patterns of interpersonal communication in Parapat Village are language and habitual barriers felt by immigrant communities. But so far the community has been able to overcome it by interacting properly and using language that has been agreed beforehand.